DIFUSI INOVASI SISTEM TUNNEL GARAM KELOMPOK JAGAD KIDUL DALAM PENGEMBANGAN KAMPUNG GARAM DI KECAMATAN MIRIT KABUPATEN KEBUMEN - Goesty Adinda Puspita Dewi; Augustin Rina Herawati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This study examines the successful diffusion of a salt tunnel system innovation among the Jagad Kidul Salt Farmers Group in Kebumen Regency. This innovation was introduced through training by the Kebumen Regency Maritime Affairs and Fisheries Office in collaboration with the Tegal Fisheries Training and Extension Center and encouraged the establishment of Kampung Garam as a model for innovation based on local adaptation. The study aims to analyze the diffusion of innovation process and the factors supporting its success. The method used was qualitative with a descriptive approach. Data collection techniques included observation, interviews, and documentation. The analysis diffusion of innovation is based on Everett M. Rogers four main elements: innovation characteristics, communication channels, timeframe, social systems, and supporting factors. The results indicate that the diffusion of innovation proceeded well and was sustainable. The innovation was deemed profitable, easy to use, testable, and easily observed. Communication channels included interpersonal communication and mass media. The innovation decision-making process encompasses the stages of knowledge, persuasion, decision, implementation, and confirmation, with adopters as the primary adopters and early adopters. Success factors include individuals, culture, knowledge, and reinvention. The researchers recommend strengthening government support, particularly in marketing, facility suitability, strengthening opinion leaders, and program transparency.